Corruption and Economic Growth: A South Korean Study - Kim, Chong-Uk; Lim, Gieyoung (Journal of Reviews on Global Economics, 2015)
Using a vector autoregressive model (VAR) with 42 years of South Korean annual data, we empirically investigate two possible links between corruption and economic growth. Even though we find negative correlations between corruption and other growth variables such as private investment, we do not find any strong empirical evidence supporting negative correlations between corruption and economic growth. Our results are similar to previous empirical findings and seem to be another empirical mismatch between micro and macro level data.